Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1128/jb.00381-17
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Intramembrane Protease RasP Activity in Escherichia coli and In Vitro

Abstract: RasP is a predicted intramembrane metalloprotease of that has been proposed to cleave the stress response anti-sigma factors RsiW and RsiV, the cell division protein FtsL, and remnant signal peptides within their transmembrane segments. To provide evidence for direct effects of RasP on putative substrates, we developed a heterologous coexpression system. Since expression of catalytically inactive RasP E21A inhibited expression of other membrane proteins in, we added extra transmembrane segments to RasP E21A, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…FtsL protein levels are normally controlled through regulated intramembrane proteolysis (RIP). FtsL contains a cytoplasmic recognition motif that is cleaved by RasP, an intramembrane zinc metalloprotease (79,80). The DivIC protein stabilizes FtsL, preventing cleavage by RasP (81).…”
Section: Sos-independent Regulation Of Cell Divisionmentioning
confidence: 99%
“…FtsL protein levels are normally controlled through regulated intramembrane proteolysis (RIP). FtsL contains a cytoplasmic recognition motif that is cleaved by RasP, an intramembrane zinc metalloprotease (79,80). The DivIC protein stabilizes FtsL, preventing cleavage by RasP (81).…”
Section: Sos-independent Regulation Of Cell Divisionmentioning
confidence: 99%
“…RseP utilizes tandem PDZ domains to recognize substrates via a size filtering rather than recognizing a specific amino acid sequence (Hizukuri et al , ). RasP contains a single PDZ domain that is also thought to function as a size exclusion filter for substrates (Parrell et al , ). In E. faecalis Eep, a metalloprotease homologous to RasP (44% identity and 62% similarity) functions as the site‐2 protease and is required for RsiV degradation and σ V activation (Varahan et al , ).…”
Section: Degradation Of Rsivmentioning
confidence: 99%
“…The DegS-cleaved form of RseA, which has lost most of its periplasmic domain, can pass through the PDZ filter and gain access to the intramembrane active site of RseP. It has been suggested that the single PDZ domain of Bacillus subtilis S2P homolog, RasP, might also act as a sizeexclusion filter (Parrell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%